Modeling and forecasting interdependence of the ASEAN-5 stock markets and the US, Japan and China - Lattayaporn K. (2017)
© Springer International Publishing AG 2016. A benefit of portfolio diversification has been designated as evidence showing a low level of stock market interdependence. Therefore, this study aims at examining the interdependence of ASEAN-5 stock markets and the US, Japan, and China in order to increase portfolio diversification benefit among those countries. We proposed the timevarying copula-based VAR model to measure the interdependence and the transmission of stock price movement. Also, a forecasting Kendall’s tau method was proposed to check robustness of the copula-based model. The main findings of this study revealed that the dynamic Kendall’s tau between the US and Indonesia, the US and Malaysia displayed tiny values. It indicates existence of opportunities to diversify an international portfolio. Moreover, the dynamic dependences also indicate that the interdependence between ASEAN-5 and China have been remaining limited. The results of IRFs showed that US had the strongest impact to ASEAN-5 while Indonesia and Malaysia had the lowest response to US, Japan, and China. In addition, the robustness check indicates that our prediction is precise.